Healthcare provider perceptions for kawan diabetes application: A qualitative study - Bernadetta Eka Noviati; Dita Hanna Febriani; Generosa Lukhayu Pritalia (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Cases of type 2 Diabetes Mellitus (DM) are increasing on a daily basis, occurring at all age levels, with the prevalence of younger sufferers increasing. Diabetes mellitus that is not detected early and is not managed well can result in serious complications, both macrovascular and microvascular. Effective screening provides a potential opportunity for people with diabetes. Objectives: This study aimed to identify the needs of healthcare providers for a web-based application to support systematic screening and integrated management of type 2 diabetes patients in hospitals. Methods: A qualitative descriptive study was conducted involving nutritionists, pharmacists, outpatient and inpatient nurses, internal medicine specialists, general practitioners, and hospital managers selected through purposive sampling. Participants had worked for at least one year, had experience managing type 2 DM patients, and were able to use electronic medical record systems. Data were collected through in-depth interviews and observations and analyzed using thematic analysis Results: Five main themes were identified: the need for comprehensive data entry features, patient identity and health information management, an attractive and user-friendly interface, notification functions, and recapitulation and educational features accessible to both healthcare providers and patients. Conclusion: Healthcare providers require a web-based application to facilitate integrated care for patients with type 2 DM, particularly for complication risk assessment using SEAR-B. The study recommends developing an integrated application connecting healthcare providers and patients to improve diabetes management and screening outcomes.